Effect of the Blended Learning Model in English Course on Students’ English Proficiency - Liu, Weiting; Lu, LeeHsing (International Journal of Sociologies and Anthropologies Science Reviews, 2026)
Background: Traditional college English instruction in China has been largely teacher-centered, which often limits student engagement and language skill development. The growing adoption of blended learning—integrating face-to-face and digital instruction—has presented a promising solution. The Superstar mobile learning platform has emerged as a tool to support this innovative approach. Objective: This study aimed to evaluate the effectiveness of Superstar-based blended learning in enhancing English language proficiency among college students. It also sought to assess students' engagement and their perceptions of the blended learning environment. Methodology: A quasi-experimental design was employed with two groups of students enrolled in a college English course at Shenyang University. The control group (n=60) received traditional instruction, while the treatment group (n=62) engaged in Superstar-based blended learning over eight weeks. Pre-tests and post-tests assessed listening, reading, and writing skills using the CET-4 framework. A 5-point Likert-scale questionnaire measured student engagement and perception. Data were analyzed using SPSS 26 through paired and independent samples t-tests. Results: Students in the treatment group showed significantly greater improvements in listening, reading, and writing scores compared to the control group (p < .05). Engagement levels were significantly higher in the treatment group across behavioral, emotional, social, and cognitive dimensions. Perception data indicated strong agreement with the pedagogical, social, and technical design of the Superstar-based learning model. Conclusion: The Superstar-based blended learning model significantly enhances college students’ English proficiency and engagement. Students positively perceived the platform’s instructional design and flexibility. These findings support the integration of mobile-based blended learning tools in college English instruction to improve educational outcomes.